Analysis The Role of Teachers In Enhancing The Creativity of Children Aged 4-5 Years at RA Arrahmany in The Hamlet of Sumur Mual, Pemenang North Lombok in The 2024/2025 Academic Year - Miyati, Hijiul; Jannah, Rauhun; Alawiyah, Tuti (Peneliti.net, 2025)
This study aims to describe the role of teachers in improving the creativity of children aged 5-6 years at RA Arrahmany Dusun Sumur Mual Kec. Pemenang Kab. North Lombok. This research was conducted at RA Pemenang in group A semester 2 of the 2024/2025 school year with 21 students, data collection by means of observation, interviews, and documentation. While to test the validity of the data using tringulation of sources and techniques. This type of research is descriptive qualitative field research by taking location at RA Arrahmany Dusun Sumur Mual Kec. Pemenang. The data sources used are primary data sources and secondary data sources.The results of research and data analysis can be concluded that the role of teachers in improving children's creativity aged 5-4 years, teachers make interesting learning strategies so that they can attract children's interest in learning, such as drawing and colouring, cutting, collaging, tracing, making games before learning activities, reciting the Koran, acting on the hadith movements that are read and also eating together. Learning activities at RA Arrahmany Dusun sumur Mual have started to run quite well. Supporting factors in learning children's creativity are through learning media, facilities and infrastructure, and the use of learning media in the school environment. The inhibiting factors for creativity in RA Arrahmany Dusun Sumur Mual are from students themselves, peers and parents.